Distribution and conservation of the narrow sub-endemic shrub, Lonicera paradoxa in Pamir-Alay, Central Asia - NAZOKAT DAMINOVA; SOBITJON NOSIROV; FERUZ AKBAROV; KOMILJON TOJIBAEV; ELDOR TEMIROV (Society for Indonesian Biodiversity, 2024)
Abstract. Daminova N, Nosirov S, Akbarov F, Tojibaev K, Temirov E. 2024. Distribution and conservation of the narrow sub-endemic shrub, Lonicera paradoxa in Pamir-Alay, Central Asia. Biodiversitas 25: 439-448. Lonicera paradoxa Pojark. (Lonicera ser. Alpigenae Pojark. ex A.Byalt) is a shrub with a geographically limited range. This species is included in the national red book lists of Uzbekistan, Kyrgyzstan, and Tajikistan and is considered one of the rare species in danger of extinction in nature. The species grows in a significant elevation from 1600 to 3200 m on the Northern slopes of the Alay Range, Central Asia. In this study, we investigated the geographic distribution of L. paradoxa based on scientific literature, herbarium data collections, and field surveys. We then modeled the current and potential future geographic distribution using Maxent. We also conducted a propagation study for its conservation under laboratory and greenhouse conditions. Our fieldwork in 2021-2022 found new records of L. paradoxa in Uzbekistan and Kyrgyzstan. We calculated the Extent of Occurrence (EOO) and Area of Occupancy (AOO) of the species, which were 5.08 km2 (VU) and 28 km2 (EN), respectively. Therefore, based on the IUCN Red List and Criteria, we recommend the conservation status of L. paradoxa as endangered (EN) in categories B2 ab (ii, iii, iv) + D. Our modeling prediction suggested that compared to the current, suitable habitat of L. paradoxa to reduce significantly in the future with very suitable habitats are expected to expand to the south and high mountain areas. For the first time, the conservation measures of L. paradoxa were carried out at the Tashkent Botanical Garden. The conducted research made it possible to preserve L. paradoxa in ex-situ conditions. The results of this research can be helpful in determining and planning measures for the protection of L. paradoxa in the territory of the Kyrgyz and Tajikistan Republics, both now and in the future.